The impact of plug-in fragrance diffusers on residential indoor VOC concentrations. Issue 4 (8th March 2023) - Warburton, Thomas; Grange, Stuart K.; Hopkins, James R.; Andrews, Stephen J.; Lewis, Alastair C.; Owen, Neil; Jordan, Caroline; Adamson, Greg; Xia, Bin
Abstract : The effect of adding a plug-in air freshener into 60 houses was hard to detect due to pre-existing VOCs from other sources; in homes with low ventilation rates however small increases in monoterpenes were seen, consistent with emission rates. Abstract : Plug-in fragrance diffusers are one of myriad volatile organic compound-containing consumer products that are commonly found in homes. The perturbing effects of using a commercial diffuser indoors were evaluated using a study group of 60 homes in Ashford, UK. Air samples were taken over 3 day periods with the diffuser switched on and in a parallel set of control homes where it was off. At least four measurements were taken in each home using vacuum-release into 6 L silica-coated canisters and with >40 VOCs quantified using gas chromatography with FID and MS (GC-FID-QMS). Occupants self-reported their use of other VOC-containing products. The variability between homes was very high with the 72 hour sum of all measured VOCs ranging between 30 and >5000 μg m −3, dominated by n /i-butane, propane, and ethanol. For those homes in the lowest quartile of air exchange rate (identified using CO2 and TVOC sensors as proxies) the use of a diffuser led to a statistically significant increase ( p -value < 0.02) in the summed concentration of detectable fragrance VOCs and some individual species, e.g. alpha pinene rising from a median of 9 μg m −3 to 15 μg m −3 ( p -value < 0.02). The observed increments were broadly in line with model-calculated estimates based on fragrance weight loss, room sizes and air exchange rates.